Pengaruh Penggunaan Aplikasi Multi APP.V.1.0 Berbasis Online Terhadap Peningkatan Kompetensi Profesional Guru Pendidikan Agama Islam di SMA Negeri 1 Gebang - Satria Wiguna; Muhammad Yasin (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
The problem of this research is that the teaching staff and students do not have special expertise in implementing multi App.V.1.0 applications. So that learning and teaching activities have not been effective and efficient due to the application of the model in using wireless internet devices so that not all teachers can operate it. Device limitations to access multiple App.V.1.0 applications are also a major problem. The purpose of the study was to determine the use of multi-app applications. V.1.0 based online in improving the competence of professional teachers at SMA Negeri 1 Gebang. The type of research used is quantitative research. The population was 28 students and took a total sampling (100%) of 28 students. Methods of collecting data using questionnaires, observations, interviews and documentation instruments. The data analysis technique used simple linear regression analysis. Results The conclusion in this study is that there is an effect between the use of Multi App.V.1.0 Applications. Online based on increasing professional competence of SMA Negeri 1 Gebang teachers by knowing the percentage of determination of the value of r xy is as follows: 0.471 x 100% = 47.1%. Thus it can be understood that the use of Multi App.V.1.0 Applications. Online-based has contributed 47.1% in one direction to the improvement of teacher professional competence at SMA Negeri 1 Gebang. The teacher's role in the activity of using Multi App.V.1.0 Applications. Online-Based is the teacher as a facilitator and organizer, which regulates how students learn and provides direction for the material in the use of Multi App.V.1.0 Applications. Online-based, which is followed by students, is easy to understand and interpret in terms of learning outcomes.